A Malay Wo(man) - Nur Izzati Binte Haji Muhammad Faisal (Nanyang Technological University, 2023)
This project investigates the unspoken issues of misogyny that have been circling the Malay community in Singapore for generations. It aims to highlight scenes of discriminating actions against Malay women and distinguish the blurred lines between cultural and religious beliefs based on the expectations of how a Malay woman should act.